Phase Transformation of a K2GeF6 Polymorph for Phosphors Driven by a Simple Precipitation–Dissolution Equilibrium and Ion Exchange; Inorganic Chemistry; Vol. 59, iss. 12 - Lang Tianchun; Fang Shuangqiang; Khan (Han) Tao; Wang Mingguang; Yang Donglin; Wang Jun; Cao Shixiu; Peng Lingling; Bitao Liu; Cai Mingsheng; Zhong Yang; Yakovlev A. N. Aleksey Nikolaevich; et al. (2020, 2020)
Title screen